PREVALENCE AND FACTORS AFFECTING THE IMMUNIZATION STATUS IN CHILDREN OF DISTRICT PESHAWAR: A COMMUNITY BASED STUDY - Danish; Mashal Aman Tarakzai; Ayaz Ahmad; Arif Mehmood Khan; Sumera Riaz; Aftab Nazir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aim: To investigate the prevalence of immunization and investigate the factors affecting immunization status of children of district Peshawar.Methods: A cross-sectional study designed was adopted to conduct the research. The source of population of the current study was all mothers visiting Hayatabad Medical Complex (HMC), Peshawar and having children aged 12 to 24 months. A sample of 151 participants, from the population was collected based on convenient sampling technique.  The data of the current study was collected through a structured questionnaire having questions regarding demographic information. The prevalence of the immunization was investigated through collecting information regarding selected vaccines, while vaccine availability factors and accessibility related factors were analyzed as factors affecting immunization status. Descriptive statistics was used to analyze the data. Bivariate analysis was conducted to identify the prevalence and factors associated with the immunization status among children. All the analysis were conducted through SPSS.Results:The study found high immunization rates, with 93.4% for BCG, 98.0% for OPV, 90.7% for Pentavalent, and 86.1% for Measles vaccines. Significant factors affecting immunization include missed doses (22.5%, p=0.000), waiting times (p